The influence of work-life balance, superior pressure, and cyberloafing on employee productivity: the moderating role of Islamic work ethic - Suseno, Gilang; Saifudin, Saifudin (Journal of Islamic Economics Management and Business (JIEMB), 2024)
This study examines the impact of work-life balance, superior pressure, and cyberloafing on employee productivity, with a particular focus on the moderating role of the Islamic work ethic. The increasing emphasis on human resources and their effective management in today’s competitive business environment highlights the need to explore these factors in detail. Using a quantitative approach, primary data were collected from 334 employees of PT. Garment in Indonesia. The analysis employed a T-test and moderated regression analysis to assess the influence of these variables on productivity. Results indicate that work-life balance positively affects productivity, while superior pressure negatively impacts it. Interestingly, cyberloafing showed a positive effect, suggesting it may serve as a mental break, enhancing focus and creativity. Islamic work ethic positively correlates with productivity but does not moderate the relationships between work-life balance, superior pressure, and cyberloafing. These findings contribute to the understanding of human resources dynamics within Islamic cultural frameworks and provide insights into improving workplace productivity.